Ferroptosis open a new door for colorectal cancer treatment - Liang, Hong; He, Xia; Tong, Yitong; Bai, Niuniu; Pu, Yushu; Han, Ke; Wang, Yi (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) was the third incidence rate and the second mortality malignant tumor in the world. The etiology and pathogenesis of CRC are complex. Due to the long course of disease and no obvious early symptoms, most patients were diagnosed as middle and late stage.CRC was prone to metastasis, most commonly liver metastasis, which was one of the leading causes of death in CRC patients. Ferroptosis was a newly discovered cell death form with iron dependence, which was driven by excessive lipid peroxides on the cell membrane. It was different from other form of programmed cell death in morphology and mechanism, such as apoptosis, pyrosis and autophagy. Numerous studies have shown that ferroptosis may play an important role in the development of CRC. For advanced or metastatic CRC, ferroptosis promised to open a new door in the setting of poor response to chemotherapy and targeted therapy. This mini review focused on the pathogenesis of CRC, the mechanism of ferroptosis and the research status of ferroptosis in CRC treatment. The potential association between ferroptosis and CRC and some challenges were discussed.